(untitled) (Italian Journal of Public Health, 2007)
Background: Long-term interventions based on the active involvement of students, carried out by properly prepared staff using didactic support material (brochures, games etc.) including the participation/involvement of mothers or associates in community interventions; seem to be the most effective ones. This study evaluates the effectiveness of nutrition education interventions carried out by teachers with active didactic methodologies. Methods: The research was carried out by administering a frequency of food intake questionnaire, before and after the intervention. To compare the answers given before and after the educational intervention the Wilcoxon-test was applied to dependent data discriminating the group with “sufficient implementation” of the project versus “insufficient implementation”. Results: Our data demonstrates that a substantial percentage of children do not report an adequate nutritional intake, making education interventions not only opportune but necessary. In both groups there was an increase in the number of subjects having breakfast, particularly in terms of bread and biscuits intake. In the group with “sufficient implementation” there was an increase in the intake of all kinds of food with respect to the previous day’s intake and a decrease in the intake of meat, fish and legumes consumed during the previous week; in the group with “insufficient implementation” only fish intake increased significantly while vegetable intake decreased in a non-significant way. So this educational intervention appears to have been particularly effective in modifying breakfast habits and reducing snack.